Asymmetric total synthesis of (−)-javaberine A and (−)-epi-javaberine A based on catalytic intramolecular hydroamination of N-methyl-2-(2-styrylaryl)ethylamine. (18th June 2021) - Uenishi, Saho; Kakigi, Rina; Hideshima, Kumiko; Miyawaki, Akari; Matsuoka, Junpei; Ogata, Tokutaro; Tomioka, Kiyoshi; Yamamoto, Yasutomo
Abstract: Asymmetric total synthesis of (−)-javaberine A and its epimer was achieved by utilizing two methods for isoquinoline synthesis, asymmetric hydroamination of N -methyl-2-(2-styrylaryl)ethylamine and Bischler-Napieralski cyclization. Intramolecular asymmetric hydroamination of N -methyl aminoalkene 4 was catalyzed by lithium amide–chiral bisoxazoline to give tetrahydroisoquinoline ( S )-laudanosine with good enantioselectivity in excellent yield. N -Demethylation of ( S )-laudanosine was accomplished by Polonovski-type reaction to give ( S )-norlaudanosine. Condensation of ( S )-norlaudanosine with homoveratric acid, and subsequent Bischler-Napieralski cyclization, LiAlH4 reduction, and O -demethylation furnished (8 R, 14 S )-(−)-javaberine A, corresponding to antipode of natural javaberine A. (8 S, 14 S )-(−)-Javaberine A, which corresponds to C14-epimer of natural javaberine A, was also successfully synthesized. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Leave this area blank for abstract info. Image 1